PENGARUH E-SERVICE QUALITY DAN E-RECOVERY SERVICE QUALITY TERHADAP E-CUSTOMER SATISFACTION DAN E-CUSTOMER LOYALTY - Tambusai, Suci Rizka Khairuna; Suharyono, Suharyono; Pangestuti, Edriana (FIA UB, 2019)
The purpose of this study is to find the impact of e-service quality and e-recovery service quality on e-customer satisfaction and e-customer loyalty in Shopee's online marketplace. This research was triggered by the increasing number of Shopee application users resulting in complaints on the services provided. This research is a type of causal research with a quantitative approach.. The sampling method is purposive sampling counted 113 responder. Data analysis in this study used the path analysis method with the help of PLS. The results of this study indicate that e-service quality and e-recovery service quality have a significant and positive effect on e-customer satisfaction and e-customer loyalty.